“I’m not so sure…”: Teacher educator action research into uncertainty - Carrie Rogers (Networks: An Online Journal for Teacher Research, 2016)
Using a framework of uncertainty that is informed by Hannah Arendt’s philosophy this foursemester action research project describes the creation and analysis of an assignment that allows teacher candidates to explore their own uncertainties in regards to the teaching profession. This action research project examines the assignment and its development over time toward the goal of encouraging teacher candidates to have a disposition that frames uncertainty or doubt as an essential and necessary part of teaching. Findings were mixed. While this study reaffirms the theoretical perspective that action research, for me as a teacher educator, is about taking pedagogical risks to improve the quality of educational processes (Elliott, 1991) teacher candidates’ dispositions toward uncertainty remain a concern. While many, in this study, saw uncertainty as inherent to teaching many also felt that these uncertainties could be remedied with the right training or experience.